2013
DOI: 10.1186/1743-422x-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of integrase inhibitor resistance from genotype through consensus linear regression modeling

Abstract: BackgroundIntegrase inhibitors (INI) form a new drug class in the treatment of HIV-1 patients. We developed a linear regression modeling approach to make a quantitative raltegravir (RAL) resistance phenotype prediction, as Fold Change in IC50 against a wild type virus, from mutations in the integrase genotype.MethodsWe developed a clonal genotype-phenotype database with 991 clones from 153 clinical isolates of INI naïve and RAL treated patients, and 28 site-directed mutants.We did the development of the RAL li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
(35 reference statements)
1
18
0
Order By: Relevance
“…Lastly, based on the implementation of the REPTree algorithm with LOOCV testing on the 13-dimensional IN mutant feature vectors, Figure 5 displays a scatter plot of actual and predicted RAL log 10 (FC) values for the 202 IN mutants in the dataset. Only a single study on predictive models of RAL resistance could be identified in the literature [16], one that is sequence-based and involves consensus linear regression utilizing a genetic algorithm, which reports a validation R 2 correlation of 0.80 (r = 0.89) that is comparable to what is achieved here with our REPTree regression models. …”
Section: Regressionsupporting
confidence: 65%
See 3 more Smart Citations
“…Lastly, based on the implementation of the REPTree algorithm with LOOCV testing on the 13-dimensional IN mutant feature vectors, Figure 5 displays a scatter plot of actual and predicted RAL log 10 (FC) values for the 202 IN mutants in the dataset. Only a single study on predictive models of RAL resistance could be identified in the literature [16], one that is sequence-based and involves consensus linear regression utilizing a genetic algorithm, which reports a validation R 2 correlation of 0.80 (r = 0.89) that is comparable to what is achieved here with our REPTree regression models. …”
Section: Regressionsupporting
confidence: 65%
“…Figure 2 (adapted from [16]) displays both a distribution of these phenotypes as well as the RAL biological cutoff of FC = 2.0 (or log 10 …”
Section: Ral Susceptibility and In Attributesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this article we extend our genetic algorithm (GA) variable selection methodology in [5] to allow for clustering in the data. We compare the performance of multi-model inference (MMI) using restricted maximum likelihood (REML) mixed-effects modeling [6,7] (MM) with ordinary least squares regression [8] (OLS) and compare GA-MMI with the commonly used penalized regression method Least Absolute Shrinkage and Selection Operator [9] (LASSO).…”
Section: Introductionmentioning
confidence: 99%